Laser-induced transformation of H3 defects in natural diamonds - S. I. Isaenko (Учёные записки Казанского университета: Серия Естественные науки)
Raman spectroscopy is a modern spectroscopic technique well-suited for diamond research. However, heating by high-power lasers can induce thermal damage to solid materials. To examine the effects of laser radiation on nitrogen defects in diamond crystals, luminescence spectra recorded during controlled laser heating at the surface of natural diamonds with green stains were analyzed. By focusing on H3 defects, the laser intensity threshold at which defect annealing or transformation occurs was identified. The findings from this study offer practical guidance on determining the frequencies of nitrogen defects in natural diamonds using luminescence spectroscopy. Such frequencies are a key typomorphic feature of diamonds and reflect important aspects of their genetic history.